Clinical significance of true umbilical cord knot: a propensity score matching study - Ohad Houri; Or Bercovich; Avital Wertheimer; Anat Pardo; Alexandra Berezowsky; Eran Hadar; Alyssa Hochberg (BMC, 2024)
Abstract Objective True umbilical cord knot (TUCK) is a rare finding that often leads to intensified surveillance and patient anxiety. This study sought to evaluate the incidence, risk factors, and obstetric and neonatal outcomes of TUCK. Methods A retrospective cohort study was conducted at a tertiary university medical center in 2007-2019. Patients with singleton pregnancies diagnosed postnatally with TUCK were identified and compared to women without TUCK for obstetric and neonatal outcomes using propensity score matching (PSM). Results TUCK was diagnosed in 780 of the 96,766 deliveries (0.8%). Women with TUCK were older than those without TUCK (32.57 vs. 31.06 years, P < 0.001) and had higher gravidity (3 vs. 2, P < 001) and a higher rate of prior stillbirth (1.76% vs. 0.43%, P < 0.01). Following covariate adjustment, 732 women with TUCK were compared to 7320 matched controls. TUCK was associated with emergency cesarean delivery due to non-reassuring fetal heart rate (2.54% vs. 4.35%, P = 0.008, OR 1.71, 95%CI 1.14-2.56) and intrapartum meconium-stained amniotic fluid (19.26% vs. 15.41%, P = 0.022, OR 1.31, 95%CI 1.04-1.65). Neonatal outcomes were comparable except for higher rates of 1-min Apgar score < 7 and neonatal seizures in the TUCK group. The stillbirth rate was higher in the TUCK group, but the difference was not statistically significant (1.23% vs 0.62%, P = 0.06, OR 1.96, 95%CI 0.96-4.03). Conclusions TUCK has several identifiable risk factors. Pregnant women with TUCK may cautiously be informed of the relatively low risks of major obstetric or perinatal complications. The lower occurrence of stillbirth in the TUCK group warrants further study.